2023
DOI: 10.3390/biom13050818
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Signaling in Cardiovascular Diseases

Abstract: Sphingosine-1-phosphate (S1P) is an important sphingolipid molecule involved in regulating cardiovascular functions in physiological and pathological conditions by binding and activating the three G protein-coupled receptors (S1PR1, S1PR2, and S1PR3) expressed in endothelial and smooth muscle cells, as well as cardiomyocytes and fibroblasts. It exerts its actions through various downstream signaling pathways mediating cell proliferation, migration, differentiation, and apoptosis. S1P is essential for the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Recently, SphK1 was found to influence S1P upregulation more than SphK2, and S1PR3 was linked to fibrotic manifestations in the lung [44]. Wang et al, 2023, reported that abnormal S1P content in the circulation affected cardiovascular disorder pathogenesis and S1PR3 mediation of cell proliferation and vascular permeability [45]. Furthermore, the S1PR3 antagonist was observed to improve graft viability in rat heart transplants [102].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, SphK1 was found to influence S1P upregulation more than SphK2, and S1PR3 was linked to fibrotic manifestations in the lung [44]. Wang et al, 2023, reported that abnormal S1P content in the circulation affected cardiovascular disorder pathogenesis and S1PR3 mediation of cell proliferation and vascular permeability [45]. Furthermore, the S1PR3 antagonist was observed to improve graft viability in rat heart transplants [102].…”
Section: Discussionmentioning
confidence: 99%
“…Sphingosine 1-phosphate (S1P) is a pleiotropic bioactive lipid mediator that is formed from the catalysis of sphingosine kinases (SphK1 and SphK2). Sphingolipids (SPLs), such as S1P, bind to S1P receptors (S1PR1-5), inducing various cellular responses, and have been implicated in many studies as key regulators of fibrosis in various tissues and organs [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], including the cornea [ 26 , 33 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation